2020
DOI: 10.1007/s11255-020-02651-3
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of platelet-to-lymphocyte ratio on the long-term renal survival in patients with IgA nephropathy

Abstract: Purpose Platelet-to-lymphocyte ratio (PLR) was established showing the poor prognosis in several diseases, such as malignancies and cardiovascular diseases. But limited study has been conducted about the prognostic value of PLR on the long-term renal survival of patients with Immunoglobulin A nephropathy (IgAN). Methods We performed an observational cohort study enrolling patients with biopsy-proven IgAN recorded from November 2011 to March 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…PLR may be more valuable than counting platelets or lymphocytes alone due to its reflection of both inflammation and thrombosis [ 22 ]. Some studies have reported the association of PLT and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLR may be more valuable than counting platelets or lymphocytes alone due to its reflection of both inflammation and thrombosis [ 22 ]. Some studies have reported the association of PLT and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…However, another research from Central China reported that there was no difference between male and female in PLR [ 33 ]. A study showed that high baseline PLR could predict poor renal survival in patients with IgAN, especially in female cases [ 22 ]. In our study, we found that the sex difference in PLR may influence the effects of PLR on mortality in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our current findings are consistent with previous studies in the non-transplant setting, showing weak or acceptable predictive values of PLR and/or NLR for prediction of postoperative pancreas-related complications following pancreatic surgery as well as a reduced ability for the prediction of the severity of the disease in acute pancreatitis [9,14,16,37,43,46]. However, after liver and kidney transplantation alone, preoperative NLR and PLR levels as well as their distinct postoperative course could be identified as independent predictors of early graft dysfunction and decreased graft survival in the long-term follow up [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-to-lymphocyte ratio (PLR) calculated as platelet count divided by lymphocyte count has been established as a novel marker of malignancies, cardiovascular diseases, and chronic obstructive pulmonary disease [21][22][23]. In Kaplan-Meier analysis, PLR more than 137 was found to be a predictive factor of poor renal outcome ESRD [24]. Both NLR and PLR were assessed as markers of inflammatory states, and their prognostic significance has been established in several conditions such as rheumatoid arthritis, solid tumors, and coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%